Metode Simple Multi Attribute Rating Technique dalam Keputusan Pemilihan Dosen Berprestasi yang Tepat - Putra, Rezi Elsya; Djasmayena, Selvia (SEULANGA SYSTEM PUBLISHER, 2020)
Each lecturer is required to carry out the tridarma of higher education, a career to become a lecturer must be professional in accordance with his knowledge and expertise. Almost every year state or private tertiary institutions, give an award to lecturers who excel one of the benchmarks is from the tri darma performance of higher education. At present in determining the right lecturer with good achievements there are still many weaknesses of one of the criteria used. Then the research has the aim to determine the outstanding lecturers by using the right criteria effectively. The method used is the Simple Multi Attribute Rating Technique (SMART) method using Sekolah Tinggi Ilmu Komputer (STIKOM) Muhammadiyah Batam’s lecturer data. The results of this study set the right criteria, so get a very high level of accuracy which is 79%. So this research becomes the right indicator in determining the outstanding lecturers.